(untitled) (Plant Tissue Culture and Biotechnology, 2010)
Key words: Auxillary buds, Eggplant, Encapsulation, Synthetic seed D.O.I. 10.3329/ptcb.v19i2.5445 Plant Tissue Cult. & Biotech. 19(2): 263-288, 2009 (December) - Short communication